Peran Pendidikan Agama Kristen terhadap Dekadensi Moral Generasi Milenial dalam Budaya Gawai Dayak - Viki Agustia; Abraham Tefbana (JURNAL LUXNOS, 2026)
The Gawai Dayak Tebidah culture is an annual post-harvest tradition expressing gratitude to God, deeply rooted in religious, social, and solidarity values. However, technological advancements and modernization have triggered a shift in meaning among the millennial generation in Nangkak Lestari Village, where sacred customary values are increasingly degraded by deviant behaviors such as revelry, drunkenness, and promiscuity. This qualitative research using a limited case study approach aims to analyze this value shift from the perspective of Christian Religious Education (PAK). Data were gathered through structured interviews with customary leaders, heads of hamlets, and millennial representatives. The results indicate that the moral decline among the youth stems from the uncritical adoption of global culture, unmatched by a solid understanding of both their traditional roots and Christian faith values. As a clinical-theological implication, this article emphasizes the crucial role of PAK and local churches in conducting contextual faith formation to reorient millennials' perspectives. Through biblically-based teachings, the millennial generation is expected to preserve the noble essence of Gawai Dayak as an expression of gratitude to Christ, avoiding both syncretism and moral decadence.